RESPON ORGANOLEPTIK CUMI-CUMI (Loligo sp) YANG DIRENDAM DENGAN MENTIMUN (Cucumis sativus) PADA DURASI DAN KONSENTRASI BERBEDA - ayu oktari; Endang Bidayani; Denny Syaputra; Ardiansyah Kurniawan (Journal of Aquatropica Asia, 2023)
Squid (Loligo sp) is one of the most essential fishery commodities and ranks third after fish and shrimp in commercial fisheries. The freshness of the squid is a very important factor and is closely related to its economic value. One of the actors in the marine commodity storage business at Rebo Beach, Bangka Regency uses Cucumbers to maintain the quality of Squid. Until now there has been no scientific research that proves that Cucumber can be used as a preservative for Squid. For this reason, it is necessary to research to examine the effect of using cucumber at different concentrations and soaking times on the organoleptic assessment of squid quality. This research was conducted in February 2020. The handling process for the Squid was carried out at the Squid shelter in Baturusa, Merawang District, Bangka Regency. In contrast, the organoleptic tests were carried out at the Aquaculture Laboratory of the University of Bangka Belitung. The research was conducted by experimental method. The research variables were differences in the concentration of grated Cucumber and differences in the length of soaking Squid. This study used RAL (Completely Randomized Design) Factorial pattern with 2 factors and 3 replications. Treatment factor by giving grated Cucumber and control or using ice cubes at different times and doses. The soaking times in this study were 24 hours and 48 hours with grated cucumber measurements of 50, 100, and 150 grams per 5 liters of water. Data analysis in this study used the Kruskarwalis test. Squid treated with grated cucumber had the same brightness level as ice cubes after 24 hours of soaking. Giving grated Cucumber does not affect the taste and texture of Squid to the level of people's preferences. Giving grated Cucumber as much as 150 g with 24 hours of soaking time can be accepted by consumers and can compete with Squid which is given ice cube treatment.